2017
DOI: 10.1016/j.ssresearch.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Why does college education matter? Unveiling the contributions of selection factors

Abstract: This study investigates the contributions of pre-college selection factors that may partially lead to the college degree – health link by using longitudinal data from the National Longitudinal Survey of Youth 1979 cohort. Propensity score matching method finds that the effects of college degree on various health outcomes (self-rated health, physical component summary index, health limitations, CESD scale) are reduced by 51% on average (range: 37%–70%) in the matched sample. Among these observed factors, cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…To compare our results with those of prior studies, we added an additional model comparing BA holders to all groups with lower schooling combined. Consistent with prior studies (Bauldry 2014;Lawrence 2017;Zheng 2017), these models reveal a clear BA threshold effect: BA completion is associated with significantly better physical and mental/global health than not completing a BA for six of the eight outcomes except hypertension and diabetes.…”
Section: Resultssupporting
confidence: 83%
“…To compare our results with those of prior studies, we added an additional model comparing BA holders to all groups with lower schooling combined. Consistent with prior studies (Bauldry 2014;Lawrence 2017;Zheng 2017), these models reveal a clear BA threshold effect: BA completion is associated with significantly better physical and mental/global health than not completing a BA for six of the eight outcomes except hypertension and diabetes.…”
Section: Resultssupporting
confidence: 83%
“…In sum, our results are largely consistent with several recent studies that encourage us to rethink the conventional wisdom when it comes to the direct effects of educational attainment (Duke and Macmillan 2016; Morin et al 2013; Olsen 2017; Zheng 2017). As researchers continue to address matters of omitted variable bias, selection effects, and reverse causality, we find that strong preliminary associations between educational attainment and later social outcomes are reduced.…”
Section: Discussionsupporting
confidence: 90%
“…We assume the college effect will decrease when controlling for adolescent self‐concept because part of the observed college effect is the mediating role it plays for adolescent self‐concept, thus lending support to prior research documenting the importance of early trajectories and their relative stability over time. It may be the case that college clearly has self‐concept benefits, but largely for those who are poised to reap those benefits in the first place (Duke and Macmillan 2016; Zheng 2017).…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, does college increase civic engagement, or are the effects we see due to selection into college? The social capital available to children early in life has a strong effect on the likelihood of their eventually graduating college (Mayger, Hochbein, and Dever 2017), and Zheng (2017) found that selection effects account for a significant proportion of the effect of college education on health outcomes, but college education remains an independent predictor of those outcomes even after accounting for selection. Much of the research on returns to higher education is about the economic returns to education, focusing on it as a private good (for reviews, see Barrow and Malamud 2015;Hout 2012) and on relative effects of educational achievement (Horowitz 2018) and overmatch (Vaisey 2006).…”
Section: Original Articlementioning
confidence: 99%